DEVELOPING LEADERSHIP IN THE DIGITAL AGE OF SCHOOL ADMINISTRATORS BASED ON KALAYANAMITTA UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE NAKHON SI THAMMARAT - Thongho, Natthaya; Yotharak, Maliwan; Samakkhi, Pricha (Journal of Educational Review Faculty of Education in MCU, 2025)
The purpose of this research article were 1) to study the developing leaderships condition in the digital age of school administrators, 2) to study the guidelines for developing leaderships in the digital age of school administrators based on the Seven Kalyṇamitta-dhamma, 3) to present the guidelines for developing leaderships in the digital age of school administrators based on the Seven Kalyṇamitta-dhamma under the secondary educational service area office Nakhon Si Thammarat. This research was mixed method research, consisting of 3 phases. In the first phase, the current condition of digital leadership was examined using a survey questionnaire administered to a sample of 337 school administrators, determined by Krejcie and Morgan’s sampling table. The data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. In the second phase, in-depth interviews were conducted with 5 key stakeholders to explore strategies for developing digital leadership based on the Seven Kalyṇamitta-dhamma. The data were analyzed using content analysis. In the third phase, a focus group discussion was conducted with 7 experts to validate and refine the proposed development guidelines. The data from the focus group were analyzed using thematic content analysis. The results showed that: 1) the findings revealed that the average scores were at a high level. When analyzed by specific aspects, it was found that all aspects scored at a high level. The aspect with the highest average score was digital network culture, followed by digital leadership, digital vision, and digital knowledge and skills, respectively while the aspect with the lowest average score was innovation and creativity. 2) The development of digital leadership should adhere to the Seven Kalyṇamitta-dhamma, which aligned with 5 components: 1. digital vision, 2. digital knowledge and skills, 3. digital network culture, 4. digital leadership, and 5. innovation and creativity. These components should be cultivated alongside the Seven Kalyṇamitta-dhamma: 1. Piyo (lovely), 2. Garu (respectable), 3. Bhvanīyo (admirable), 4. Vatt (knowing how to speak effectively), 5. Vacanakkhamo (patient with words), 6. Gambhīrañaca Katha Katt (explaining profound matters), 7. No Caṭṭhne Niyojaye (not leading to degradation). 3) The guidelines presentation for developing leaderships in the digital age of school administrators based on the Seven Kalyṇamitta-dhamma were found to be appropriate, feasible, and beneficial.